Evaluation of Antioxidant, Antimicrobial, and Cytotoxic Activities and Correlation with Phytoconstituents in Some Medicinal Plants of Nepal - Keshav Ranabhat; Kamal Prasad Regmi; Sarwesh Parajuli; Ranjita Thapa; Arjun Prasad Timilsina; Saurav Katuwal; Shantel Fleming; Akkal Dev Mishra; Khaga Raj Sharma; Bishnu P. Regmi (Journal of Chemistry)
Traditional herbal medicines have been consumed in Nepal and other parts of the eastern hemisphere since ancient times. Many of these plants reportedly have been effective against ailments as well. This study aims to analyze the phytochemical constituents from the extracts of ten such plants and evaluate their antimicrobial, cytotoxicity, and antioxidant properties. In addition, the study aims to study the correlation of cytotoxicity and antioxidant activities with the total phenolic, flavonoid, and tannin contents. The plants investigated were Oroxylum indicum, Kalanchoe pinnata, Phragmites vallatoria, Ehretia acuminata, Cirsium wallichii, Ampelocissus tomentosa, Dichrocephala integrifolia, Boenninghausenia albiflora, Cynoglossum zeylanicum, and Clerodendrum serratum. Phytochemical analyses were performed to evaluate secondary metabolites, such as glycosides, flavonoids, terpenoids, saponins, alkaloids, and fats. The total phenolic contents of the extracts ranged from 14.94 to 229.89 mg GAE/g, the total flavonoid contents varied from 66.67 to 900 mg QE/g, and the total tannin contents were 42 to 168 mg GAE/g. The results of the antioxidant studies showed that the highest antioxidant activity was exhibited by the extract of A. tomentosa (IC50 = 7.89 µg/mL) followed by E. acuminata (IC50 = 24.82 µg/mL) and C. serratum (IC50 = 32.91 µg/mL). The extracts from P. vallatoria and A. tomentosa exhibited substantial antimicrobial activity. The extracts of A. tomentosa and B. albiflora showed lethality against brine shrimp with LC50 values of 33.11 µg/mL.